Evaluation of smart and sustainable cities through a hybrid MCDM approach based on ANP and TOPSIS technique - Ozkaya, Gokhan; Erdin, Ceren (ELSEVIER SCI LTD, 2020)
Significant efforts are being performed to make cities smarter and more sustainable. Therefore, there is a need to compare these efforts using evaluation frameworks. According to the literature review, the basic dimensions of smart cities are generally evaluated with the criteria of regional competitiveness, transportation, information and communication technology, economy, natural resources, human and social capital, quality of life and participation of citizens in the management of cities. In this paper, Analytical Network Process (ANP) is used to weight smart and sustainable city criteria. According to the results, while 'smart living' is the most important characteristic with a 35,459% priority, 'smart governance' is the last with 5,738%. The study covers 44 cities around the world and comparisons were made by TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). According to the results, Tokyo, London and New York are in the top three in the overall ranking. But none of these cities is among the top five in terms of smart governance, mobility and environmental dimensions. According to the results obtained, the article provides some recommendations for the cities. These results aim to help cities understand their situation relative to other cities and to see areas where policymakers need to strengthen.
Keywords: Smart city; Sustainable city; Quality of life; Smart governance; Smart people; Innovative spirit; Analytic network process (ANP); TOPSIS; Business; Economics; Sociology; Tourism; Multi criteria decision making (MCDM); CITY; PRIORITIZATION; FRAMEWORK; RANKING; MODEL; Science & Technology - Other Topics